Contribution of Pedagogical Competence and Transformational Leadership of the Principal to the Implementation of the Tasks of Design and Build Teachers at SMKN 1 Padang - Melda Fajra; Jalius Jama; Sukardi Sukardi; Danyl Mallisza; Mukhnizar Mukhnizar; Oskah Dakhi (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to reveal and analyze how much (1) the contribution of pedagogical competence to the implementation of teacher duties, (2) the contribution of principals' transformational leadership to the implementation of teacher duties and (3) the contribution of pedagogical competence and principals' transformational leadership to the implementation of teacher duties of SMKN 1 Padang both individually and together. This research uses a quantitative approach. The population is all teachers at SMKN 1 Padang totaling 89 people, while the sample is 56 people determined by Stratified Proportional Random Sampling technique and the strata used are educator certification and length of service. Data were obtained using a Likert scale questionnaire that had been tested for validity and reliability. The results of data analysis show that (1) pedagogical competence contributes significantly to the implementation of teacher duties by 19.2%. (2) principals' transformational leadership significantly contributed 8.2%, while (3) pedagogical competence and principals' transformational leadership together contributed 24%. Data analysis has shown that the three hypotheses can be accepted empirically. From the findings, it can be concluded that pedagogical competence and principals' transformational leadership are two independent variables that have a positive impact on the dependent variable of teachers' task implementation. To improve the implementation of the duties of teachers of SMKN 1 Padang, it is necessary to improve through pedagogical competence and transformational leadership of principals properly and responsibly.